Introduction of Eucalyptus spp. into the United States with Special Emphasis on the Southern United States. (17th January 2013) - Kellison, R. C.; Lea, Russ; Marsh, Paul
Abstract : Introduction of Eucalyptus spp. into the United States from Australia on a significant scale resulted from the gold rush into California in 1849. Numerous species were evaluated for fuel, wood products, and amenity purposes. The first recorded entry of eucalyptus into the southern United Stated was in 1878. Subsequent performance of selected species for ornamental purposes caused forest industry to visualize plantations for fiber production. That interest led the Florida Forestry Foundation to initiate species-introduction trials in 1959. The results were sufficiently promising that a contingent of forest products companies formed a cooperative to work with the USDA Forest Service, Lehigh Acres, FL, USA, on genetic improvement of selected species for fiber production. The Florida initiative caused other industrial forestry companies in the upper South to establish plantations regardless of the species or seed source. The result was invariably the same: failure. Bruce Zobel, Professor of Forestry, North Carolina State University, initiated a concerted effort to assess the potential worth of eucalyptus for plantation use. The joint industrial effort evaluated 569 sources representing 103 species over a 14-year period. The three levels of testing, screening, in-depth, and semioperational trials led to identification of some species and sources that offered promise for adaptation, but severe winter temperatures in late 1983 and early 1984 and 1985 terminated the project. Despite the failed attempt valuable silvicultural practices were ascertained that will be beneficial to other researchers and practitioners when attempts are again made to introduce the species complex into the US South.